Determinants of Vaccine Hesitancy and Refusal in Children of District Swabi Khyber Pakhtunkhwa, Pakistan - Syed Sajid Hussain Shah; Bibi Aalia; Mubarak Zeb; Ihsan Ullah (Gandhara University, 2022)
OBJECTIVES: The objective of the study was to evaluate factors associated with vaccine hesitancy and refusal at District Swabi, Khyber Pakhtunkhwa. METHODOLOGY: This cross-sectional study was conducted at a teaching hospital of Khyber Pakhtunkhwa District Swabi over a period of four months. Children between the ages of 9 months to 10 years from the local population admitted to the children ward/daycare centre were included in the study. Parents were inquired about vaccination status and in case of no vaccination or partial vaccination; then the reason was inquired after proper informed consent. Data were collected by using a structured proforma and analyzed using SPSS-24. RESULTS: A total of 828 children were included in this study. Out of these 492 (59.4%) were male and 336 (40.6%) were females. Of the total 828 children, 753 (90.9%) were vaccinated up to date, 48 (5.8%) were not vaccinated and 27 (3.3%) were partially vaccinated. Under vaccinated were 75 patients, 52% were left out due to misconception/beliefs, 6% patients were having issues due to living far away, 2.7% patients could not be vaccinated due to presence of other diseases and 37.3% due to lack of knowledge regarding vaccination. A significant correlation was found between the vaccination status of children and aforementioned reasons (p-value ≤0.001). CONCLUSION: The most common cause of not vaccinating children with polio vaccines was misconceptions/beliefs and lack of knowledge of the parents.